Functional Outcome of an Anatomically Contoured Locking Plate in Intra-Articular Pilon Fracture with MIPO Technique - Aatir Javaid, Usman Amjad, Muhammad Asif, Syed Wasif Ali Shah, Izza Nasir, Saman Shahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the outcome of osteosynthesis by using anatomically contoured locking plates in the management of intraarticular fractures of tibial plafond with minimally invasive plate osteosynthesis (MIPO) technique Methods: All the 50 patients presenting with intra-articular fractures (Pilon fracture type B and C) in the Accident and Emergency (A&E) department were included in this study. The patients involved in high-energy trauma were treated according to advanced trauma life support guidelines for any associated life- or limb-threatening injuries. The clinical, functional, and radiographic plain anteroposterior and lateral radiographs) evaluations were conducted at 6 months according to Modified Klemm and Borner scoring system and outcome variables i.e. excellent to good was labeled. Results: There were 76% males and 24% females. Most of the patients 23(46%) were in >45 years, age group. Among 50 patients, 28(56%) had type-B fractures, while 22(44%) had type-C fractures. 36(72%) had BMI <30, while 14(28%) had BMI ≥30. 3(6%) had wound infections. Among 50 patients, 41(82%) had an excellent-good outcome. A good outcome was seen in male patients (78%), as compared to female patients. A good outcome was observed in 39% of patients with age greater than 45 years followed by 32% in 18-30 years. An almost equal percentage of good (56-44%) and poor (55.6-44.4%) outcomes were reported in both types of fractures. 70.7% of patients with BMI <30 reported a good outcome. A good outcome was observed in 41 patients who do not have wound infection. However, 6 patients reported a poor outcome who didn’t have wound infection. Conclusion: Plate osteosynthesis using anatomically shaped locking plates via minimally invasive method is an efficient way of stabilization for distal tibia fracture when considering union rates and final functional outcome.